A COMPARISON OF THE EARLY CHILDHOOD CURRICULA IN HONG KONG AND SINGAPORE – FROM THE PERSPECTIVE OF MATHEMATICS EDUCATION - LAO, Kam Ling (PEOPLE: International Journal of Social Sciences, 2015)
Primary and secondary students from Hong Kong and Singapore outperformed students of many countries in mathematics in international studies. Whereas early childhood education is the foundation of elementary education, this paper aims to compare the early childhood curriculum documents of the two cities from the perspective of mathematics education and investigate the similarities and differences, if any, in their curricular intention of mathematics learning and teaching. The curricula are compared from three aspects: (1) the organization of curriculum framework; (2) the orientation of the mathematics-related content; and (3) the focuses of the mathematics-related content. It is found that both cities consider mathematics as an important and distinct learning domain in early childhood education. The analysis result shows that the two cities organize mathematics domain differently in terms of the levels of specification and the areas of emphases. The two curricula have their own characteristics as the two cities differ in cultural context and curriculum is context-specific. In light of the identified differences and similarities, the paper suggests Hong Kong to formulate learning outcomes with closer academic links and explicit expectation with respect to children’s cognitive development in mathematics. It is also suggested Singapore to elaborate the teach Principles and the PRAISE Dispositions with mathematics-related examples.